The Glutaminase-Dependent System Confers Extreme Acid Resistance to New Species and Atypical Strains of Brucella - Freddi, Luca; Damiano, Maria A.; Chaloin, Laurent; Pennacchietti, Eugenia; Al Dahouk, Sascha; Köhler, Stephan; De Biase, Daniela; Occhialini, Alessandra (Frontiers in Microbiology, 2017)
Neutralophilic bacteria have developed specific mechanisms to cope with the acid stress encountered in environments such as soil, fermented foods- and host compartments. In Escherichia coli, the glutamate decarboxylase (Gad)-dependent system is extremely efficient: it requires the concerted action of glutamate decarboxylase (GadA/GadB) and of the glutamate/GABA antiporter, GadC. Notably, this system is operative also in new strains/species of Brucella, among which Brucella microti, but not in the “classical” species, with the exception of marine mammals strains. Recently, the glutaminase-dependent system (named AR2_Q), relying on the deamination of glutamine into glutamate and on GadC activity, was described in E. coli. In Brucella genomes a putative glutaminase (glsA)-coding gene is located downstream the gadBC genes. We found that in B. microti these genes are expressed as a polycistronic transcript. Moreover, using a panel of Brucella genus-representative strains we show that the AR2_Q system protects from extreme acid stress (≤pH2.5), in the sole presence of glutamine, only the Brucella species/strains predicted to have functional glsA and gadC. Indeed, mutagenesis approaches confirmed the involvement of glsA and gadC of B. microti in AR2_Q and that the acid-sensitive phenotype of B. abortus can be ascribed to a Ser248Leu substitution in GlsA, leading to loss of glutaminase activity. Furthermore, we found that the gene BMI_II339, of unknown function and downstream the gadBC-glsA operon, positively affects Gad- and GlsA-dependent AR. Thus, we identified novel determinants that allow newly discovered and marine mammals Brucella strains to be better adapted to face hostile acidic environments. As for significance, this work may contribute to the understanding of the host preferences of Brucella species and opens the way to alternative diagnostic targets in epidemiological surveillance of brucellosis.